Immobilization of mushroom polyphenol oxidase on poly(allyl glycidyl ether-co-ethylene glycol dimethacrylate) macroporous beaded copolymers - Vaidya, Bhalchandra K.; Karale, Abhijeet J.; Suthar, Hitesh K.; Ingavle, Ganesh C.; Pathak, Tara Sankar; Ponrathnam, S.; Nene, Sanjay (Reactive & Functional Polymers, 2007)
Functional, macroporous, beaded copolymers containing epoxy groups were synthesized for immobilization of polyphenol oxidase (PPO) from edible mushroom (Agaricus bisporus). The effect of incorporation of two different sets of monomers such as glycidyl methacrylate (GMA) and allyl glycidyl ether (AGE) and the effect of cross-linking agent ethylene glycol dimethacrylate (EGDM) with varying cross-link densities on binding and expression of mushroom PPO activity were studied. The effect of porogen viz. cyclohexanol and hexanol on PPO immobilization was studied. AGE copolymers with hexanol as a porogen were found to give higher binding and expression of PPO activity than GE polymers. Crosslinking of amino groups of enzyme with 5% glutaraldehyde for 6 h gave a stable binding of PPO on AGE-75(Hex) polymer with storage half-life of approximately 25 days. Under optimum conditions, AGE-75(Hex) polymer gave 70.3% of activity yield while percent retention of PPO activity was found to be 83.5%. Immobilized PPO showed a broader pH, higher temperature and excellent storage stability. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: cross-linking agent; Enzyme immobilization; Epoxy-activated support; mushroom PPO

Integrated process for extraction and purification of alcohol dehydrogenase from Baker's yeast involving precipitation and aqueous two phase extraction - Madhusudhan, M. C.; Raghavarao, K. S. M. S.; Nene, Sanjay (Biochemical Engineering Journal, 2008)
The potential of aqueous two phase extraction for the purification of alcohol dehydrogenase (ADH) from Baker's yeast (Saccharomyces cerevisiae) is demonstrated. An integrated process involving precipitation followed by aqueous two phase extraction (ATPE) is used for effective recovery of the enzyme. This is carried out in two schemes. In the first scheme, ammonium sulphate precipitation is carried out followed by ATPE of the precipitate after suspending it in buffer. While the second scheme involves polyethylene glycol precipitation followed by ATPE of the supernatant. The effect of various process parameters such as molecular weight of polymer, tie line length, phase volume ratio and neutral salt is investigated for enhancing the activity recovery of ADH. First scheme resulted in about 85% enzyme activity recovery of ADH with purification factor of 4.2 while the second scheme about 90% enzyme activity recovery with 6.6-fold purification. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Alcohol dehydrogenase; aqueous two phase extraction; enzyme extraction; Precipitation; Purification; Yeast

Influence of cultivar, ripeness, blanching, drying, irradiation, and pectin recovery on alk(en)ylresorcinols in mango peels - Geerkens, Christian Hubert; Miller-Rostek, Petra; Matejka, Anna Elisabeth; Nene, Sanjay; Kammerer, Dietmar Rolf; Carle, Reinhold; Schweiggert, Ralf Martin (European Food Research and Technology, 2015)
The influence of different technological treatments on alk(en)ylresorcinol (AR) contents and pattern in mango peels was evaluated using peels from six different mango cultivars. AR concentrations were shown to highly depend on the cultivar. While high AR concentrations were observed in the analyzed monoembryonic cultivars, AR contents in the polyembryonic cultivar Nam Dokmai were significantly lower. Furthermore, for monoembryonic cultivars, AR levels in the peels of ripe fruits were found to be higher than in unripe ones, while AR levels in cv. Nam Dokmai were independent of the ripeness degree. Convective oven drying resulted in a significant reduction in AR contents when compared to lyophilization. Blanching prior to drying diminished AR yields, thus being unsuitable for satisfactory AR recovery. Gamma irradiation did not significantly affect the AR contents. Since depectinization of mango peels significantly concentrated AR amounts in the depectinized pomace, the consecutive extraction of pectin and ARs allows the dual valorization of mango peels. Considering the treatments investigated, the retention of ARs carrying saturated and unsaturated side chains did not differ under acidic conditions, heating, and irradiation, respectively. Consequently, the 1,3-dihydroxybenzene structure was concluded to be the most labile moiety of the AR molecule.
Keywords: Alkylresorcinol; By-products; Monoembryonic; Polyembryonic; Pomace; Ultrasound